Bioaccessibility of methylmercury, potentially toxic elements at trace or essential levels in seafood by in vitro gastrointestinal simulation: perspectives and challenges - Leonardo Dias Nascimento; André Luiz Sampaio da Silva Junior; Gregório Mateus Santana; Herick Macedo Santos; Maria Graças Andrade Korn; Rafaella Regina Alves Peixoto; Raildo Mota de Jesus (Applied Food Research)
This study reviewed the bioaccessibility of methylmercury and potentially toxic elements at trace or essential levels in seafood, through in vitro simulation. It highlights how variables such as shellfish species, geographic origin, and consumption form influence the bioaccessibility of these elements in the samples. For this purpose, a detailed literature was searched in Scopus, Web of Science™, PubMed® and Science Direct®, where 56 eligible articles (published between January 2014 and August 2024) from different regions were selected. The results highlighted a focus on methylmercury and potentially toxic elements at trace levels in shellfish, such as arsenic, cadmium, lead and mercury, which pose significant risks to human health. Culinary preparation methods can affect the bioaccessibility of these elements, showing the importance of considering these aspects when assessing food safety. The review highlighted the lack of standardization in analysis methodologies, pointing out the need for uniform guidelines to ensure replicability and the possibility of comparison between the results obtained. The introduction of the INFOGEST protocol was a significant advance in this regard, but its adoption is still limited among the studies reviewed. Furthermore, challenges and future perspectives were discussed, including the need to assess the real clinical impacts of exposure to methylmercury and elements in populations that consume seafood.